2016
DOI: 10.1039/c5tb02747k
|View full text |Cite
|
Sign up to set email alerts
|

Substrate modulus regulates osteogenic differentiation of rat mesenchymal stem cells through integrin β1 and BMP receptor type IA

Abstract: Osteoblast differentiation of mesenchymal stem cells is regulated by both soluble factor (e.g., bone morphogenetic proteins (BMP)) and mechanically transduced signaling, but the mechanisms have only been partially elucidated. In this study, physical association of BMP Receptor I (BMPRI) with integrin β1 sub-unit (Iβ1) was hypothesized to mediate osteoblast differentiation of rat bone marrow-derived mesenchymal stem cells (MSCs) on bone-like substrates. The effects of substrate modulus on osteoblast differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…Neural differentiation is favored in soft substrate, whereas moderate substrate stiffness appreciates chondrogenic differentiation. Similarly, the stiffer substrate encourages osteogenic differentiation in stem cells [111][112][113]. These results suggested that the elastic modulus of native tissue is similar to the elastic modulus of stem cell differentiation; thereby, osteogenic differentiation is favored when a stiff scaffold is used [114].…”
Section: Interventions In Actin Remodeling and Their Effect On Msc DImentioning
confidence: 86%
“…Neural differentiation is favored in soft substrate, whereas moderate substrate stiffness appreciates chondrogenic differentiation. Similarly, the stiffer substrate encourages osteogenic differentiation in stem cells [111][112][113]. These results suggested that the elastic modulus of native tissue is similar to the elastic modulus of stem cell differentiation; thereby, osteogenic differentiation is favored when a stiff scaffold is used [114].…”
Section: Interventions In Actin Remodeling and Their Effect On Msc DImentioning
confidence: 86%
“…MSCs with a small surface area (Frith, Mills, & Cooper-White, 2012;Guo, Lu, Merkel, Sterling, & Guelcher, 2016;Koçer & Jonkheijm, 2017;Wang et al, 2013). Therefore, for studies investigating the Cells on SLBs with 0.5 μM RGD showed more phospho-paxillin clusters than on SLBs with 0.2 or 1.0 μM RGD.…”
Section: Ligand Mobility and Density On Rgdfunctionalized Slbs Affementioning
confidence: 99%
“…MSCs with a small surface area (Frith, Mills, & Cooper-White, 2012;Guo, Lu, Merkel, Sterling, & Guelcher, 2016;Koçer & Jonkheijm, 2017;Wang et al, 2013). Therefore, for studies investigating the effect of substrate stiffness and ligand presentation on preosteoblast morphology, it should be established whether there is a relation between pre-osteoblast morphology and the osteogenic state.…”
Section: Ligand Mobility and Density On Rgdfunctionalized Slbs Affementioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported that the substrate modulus of 2D films regulates tumor cell expression of the transcription factor Gli2 and parathyroid hormone-related protein ( PTHrP ), both of which have been associated with bone destruction [ 5 , 6 ]. However, in the 3D bone microenvironment, cells are exposed to mechanical forces resulting from surface curvature [ 26 ] in addition to the substrate modulus, which stimulates mechanically transduced signaling in tumor [ 6 ] and bone [ 27 , 28 ] cells. To more accurately recapitulate the mechanical and morphometric properties of the bone microenvironment, we fabricated 3D scaffolds with tunable substrate moduli and pore size using a templated-Fused Deposition Modeling (3D t-FDM) process [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%